Study of Soil Carbon Reserves in Conservation Area in Gili Meno, North Lombok - Akbar, Sandi; Sukartono, Sukartono; Kusumo, Bambang Hari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Gili Meno is a small island located to the north of Lombok Island which is included in a conservation area with high potential as a tourist destination. As a tourist destination, there has been a conversion of green land into hotels and other tourist facilities which has led to changes in land use patterns. In order to reduce the increase in earth's surface temperature due to green house gas (GHG) emissions, especially CO2, CO2 mitigation efforts are needed by squesting carbon into the soil. Research on soil carbon stocks on Gili Meno has been carried out using descriptive methods with survey techniques, namely by taking soil samples in several types of land cover at two depths, namely 0-10 cm and 10-20 cm. The soil samples taken were used for analysis of C-Organic and some physical characteristics of the soil. Based on the data obtained, mangrove land cover has the largest potential carbon reserves, namely 89.36 tons.ha-1, then followed by shrub land cover, then coconut plantations, and finally open land and settlements with values respectively 57.50 ton.ha-1, 44.11 ton.ha-1, and 36.15 ton.ha-1. The high soil carbon reserves in the mangrove ecosystem compared to other land covers reflect that the carbon storage potential of mangrove land covers is better compared to other land cover types. Thus, for long-term land management, the sustainability of mengrove plants must be maintained.